Polymorphism of pfcrt K76T and pfatpase6 S769N Genes in Malaria Patients at Papua, Indonesia - Eka W. Suradji; Henry Ng; Ratih Finisanti; Eni Indrawati; Andreas Ciokan; Melisa I. Barliana; Rizky Abdulah (Pharmacology and Clinical Pharmacy Research)
Indonesia is one of the country with the highest prevalence of malaria infections. In order to achieve malaria control as an act to support Millenium Development Goals, complete eradication of Plasmodium parasites needs to be conducted. Drugs resistance has been a hindrance in this act. This study aimed to assess Plasmodium parasite resistance towards chloroquine (CQ) and artemisinin combined therapy (ACT) through the determination of polymorphism on pfcrt K76T and pfatpase6 S769N genes, respectively. Subjects of this study were 16 adult patients positively diagnosed with malaria infection caused by P. falciparum or cross infection. DNA obtained from patient blood samples were amplified using polymerase chain reaction (PCR) and then the fragment of pfcrt and pfatpase6 were then digested using ApoI and DdeI, respectively. The results showed that 81% of the pfcrt K76T polymorphism was occured on the samples, which indicated the resistance of CQ. Meanwhile, 87% of the patient samples did not showed any polymorphism of pfatpase6 S769N gene, which indicated no resistance of ACT. This study showed that CQ was no longer effective as the first line therapy of antimalarial drugs due to the resistance of P. falciparum to CQ. However, the used of ACT still can be maintained in the antimalarial drug therapy regimen. In conclusion, the polymorphism of both genes negatively influenced the effectivity of antimalarial therapy using artemisinin.Keywords: antimalarial drugs, resistance, polymorphism, endemic area